Correlation studies between electronic nose response and headspace volatiles of Eurycoma longifolia extracts - Shafiqul Islam, A.K.M.; Zhari, Ismail; Bahruddin, Saad; Abdul Rahman, Othman; M. Nizam, Ahmad; Ali Yeon, Md Shakaff (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com